Comparison of Effectiveness of Milling Time of Avocado Seed Extract for Lowering Blood Glucose Level in Alloxan-induced Diabetic Rat - Manalu, Jojor Lamsihar; Caesarlia, Josephine; Dewi, Rita (Journal of Urban Health Research, 2025)
Introduction:Diabetes Mellitus (DM) is a chronic metabolic disorder with increasing global prevalence. Effective management is crucial to prevent acute and long-term complications. Natural products, including avocado (Persea americana Mill.) seeds, have gained attention for their potential antidiabetic properties due to their rich phytochemical content. Methods: This experimental study used male Sprague Dawley rats, divided into two main groups based on blood glucose status (normal and diabetic), with each group further subdivided based on the milling duration of avocado seed extract (5 and 10 minutes). The extract was administered orally at a dose of 250 mg/kg body weight for seven consecutive days. Blood glucose levels were measured using a glucometer before and after the treatment period. Results: Avocado seed extract demonstrated a glucose-lowering effect in both treatment groups. Rats treated with extract milled for 5 minutes showed a mean reduction in blood glucose of 25.13 mg/dL, while those receiving extract milled for 10 minutes exhibited a greater reduction of 45.88 mg/dL. Although the group treated with the 10-minute extract showed a higher decrease, statistical analysis using the Mann–Whitney U test revealed no significant difference in glucose-lowering efficacy between the two milling durations (P > 0.05). Conclusions:Avocado seed extract, regardless of milling duration, has potential antihyperglycemic effects in alloxan-induced diabetic rats. However, the variation in milling time between 5 and 10 minutes did not significantly influence the extract’s effectiveness. Further research with longer intervention periods, standardized phytochemical content, and inclusion of a positive control is recommended to validate its therapeutic potential. Keywords: Avocado Seed Extract; Blood Glucose; Diabetes Mellitus; Sprague Dawley Rats; Milling Duration